Wanprestasi Developer dalam Jual Beli Kavling: Hilangnya Kepastian Hukum bagi Konsumen: Developer’s Default in Land Lot Sales: The Loss of Legal Certainty for Consumers - Ade Irawan; Choirihi, Muchammad; Kukuh Sudarmanto; Zaenal Arifin (Universitas Semarang, 2025)
This study aims to analyze the forms of legal liability that developers must fulfill toward buyers of land lots situated on legally problematic land and examine the legal protection measures available to buyers in addressing such issues. The research is motivated by developers' growing practice of land lot sales that often lack guarantees of legal certainty, particularly when the land object is subject to administrative or legal disputes. This study uses a normative and sociological approach to explore the relationship between developers’ legal obligations and consumer protection in property transactions. The findings indicate that developers are legally required to fulfill contractual performance and provide restitution or compensation in breach cases, as stipulated in the Civil Code and the Consumer Protection Law. On the other hand, buyers are entitled to seek remedies through litigation and non-litigation channels, including the Consumer Dispute Settlement Board (BPSK). Developers’ liability is repressive and preventive, emphasizing the need to ensure the legality and dispute-free status of the land object before marketing. The implications of this study highlight the importance of strengthening regulatory frameworks, enhancing government oversight, and promoting consumer legal literacy to achieve legal certainty and fairness in property transactions. Penelitian ini bertujuan untuk menganalisis bentuk pertanggungjawaban hukum yang harus dipenuhi oleh developer terhadap pembeli kavling tanah pada objek yang bermasalah secara hukum, serta menelaah upaya perlindungan hukum yang dapat diberikan kepada pembeli dalam menghadapi permasalahan tersebut. Latar belakang penelitian ini didasarkan pada meningkatnya praktik jual beli kavling tanah oleh developer tanpa jaminan kepastian hukum, terutama ketika objek tanah masih berstatus sengketa administratif maupun yuridis. Penelitian menggunakan pendekatan normatif dan sosiologis untuk mengidentifikasi hubungan antara kewajiban hukum developer dan perlindungan hak-hak konsumen. Temuan menunjukkan bahwa developer berkewajiban memenuhi prestasi sesuai perjanjian pengikatan jual beli serta memberikan restitusi dan kompensasi apabila terjadi wanprestasi, sebagaimana diatur dalam Kitab Undang-Undang Hukum Perdata dan Undang-Undang Perlindungan Konsumen. Pembeli berhak menempuh upaya hukum melalui jalur litigasi maupun non-litigasi, termasuk Badan Penyelesaian Sengketa Konsumen (BPSK). Pertanggungjawaban hukum developer bersifat tidak hanya represif tetapi juga preventif, dengan memastikan legalitas dan bebas sengketa atas objek tanah sebelum dipasarkan. Implikasi penelitian ini menegaskan pentingnya penguatan regulasi, peningkatan pengawasan pemerintah, dan pemberdayaan konsumen melalui literasi hukum guna mewujudkan kepastian hukum serta keadilan dalam transaksi properti.